Sensitivity of Antarctic phytoplankton species to ocean acidification: Growth, carbon acquisition, and species interaction. (3rd May 2013) - Trimborn, Scarlett; Brenneis, Tina; Sweet, Elizabeth; Rost, Björn
Abstract : Despite the fact that ocean acidification is considered to be especially pronounced in the Southern Ocean, little is known about CO2 ‐dependent physiological processes and the interactions of Antarctic phytoplankton key species. We therefore studied the effects of CO2 partial pressure (PCO2 ) (16.2, 39.5, and 101.3 Pa) on growth and photosynthetic carbon acquisition in the bloom‐forming species Chaetoceros debilis, Pseudo‐nitzschia subcurvata, Fragilariopsis kerguelensis, and Phaeocystis antarctica. Using membrane‐inlet mass spectrometry, photosynthetic O 2 evolution and inorganic carbon (Ci ) fluxes were determined as a function of CO2 concentration. Only the growth of C. debilis was enhanced under high PCO2 . Analysis of the carbon concentrating mechanism (CCM) revealed the operation of very efficient CCMs (i.e., high Ci affinities) in all species, but there were species‐specific differences in CO2 ‐dependent regulation of individual CCM components (i.e., CO2 and uptake kinetics, carbonic anhydrase activities). Gross CO2 uptake rates appear to increase with the cell surface area to volume ratios. Species competition experiments with C. debilis and P. subcurvata under different PCO2 levels confirmed the CO2 ‐stimulated growth of C. debilis observed in monospecific incubations, also in the presence of P. subcurvata . Independent of PCO2, high initial cell abundances of P. subcurvata led to reduced growth rates of C. debilis . For a better understanding of future changes in phytoplankton communities, CO2 ‐sensitive physiological processes need to be identified, but also species interactions must be taken into account because their interplay determines the success of a species.